Comprehensive analysis of gene expressions in ileal mucosa of chickens fed paddy rice and their IgA response to oral vaccination - M. Yamamoto; A. Ueno; H. Watanabe; M. Okamoto; K. Furukawa; A. Murai (Poultry Science)
Paddy rice ingestion increases intestinal mucin secretion and production by enhancing MUC2 gene expression and epithelial turnover. In this study, we performed a comprehensive analysis of intestinal gene expression in chickens fed paddy rice and investigated whether the intestinal IgA response was modified by paddy rice ingestion. Furthermore, we investigated the possible involvement of gut fermentation. Layer male chicks were divided into two groups according to diet i.e., corn or paddy rice at 650 g/kg diet, which were given for 14 consecutive days at 7 d of age. The ileal gene expression levels in both groups were compared using DNA microarray analysis. A total of 120 genes were upregulated >1.5-fold in the paddy rice group, whereas 159 genes were downregulated <1.5-fold. Remarkably, the gene expression levels of immunoglobulin heavy chain α (IGHA), immunoglobulin J chain (IGJ), and immunoglobulin light chain λ chain region (IGLL1), which constitute immunoglobulin A, decreased 3–10 times in the paddy rice group. Infectious bursal disease virus (IBDV) vaccine were orally administered to chickens fed corn or paddy rice to examine the intestinal immune response. Paddy rice ingestion diminished both the total IgA concentration and IBDV-specific IgA in the bile. Cecal total short-chain fatty acid and butyric acid concentrations decreased by 30 % in the paddy rice group compared to those in the corn group. In conclusion, feeding paddy rice to chickens decreased intestinal IgA production, which was partly attributable to the low fermentability of paddy rice in the intestinal tract.